2009
DOI: 10.1007/s10709-009-9393-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of a local population of Oryza glumaepatula using SSR markers: implications for management and conservation programs

Abstract: Knowledge of natural diversity and population structures of wild species, which might be related to cultivated species, is fundamental for conservation and breeding purposes. In this study, a genetic characterization of a large population of Oryza glumaepatula, occurring in a 10 km(2) area located at Tamengo Basin (Paraguay River, Brazil), was performed using SSR markers. This population is annually dragged from the river to permit navigation; one goal of this study was to examine the impact of this removal on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
2
1
1
Order By: Relevance
“…This population may be large enough to preserve a significant proportion of the original genetic diversity. Similar results were found for other large and similarly interconnected populations in Brazil ( Buso, Rangel & Ferreira, 1998 ; Vaz et al, 2009 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This population may be large enough to preserve a significant proportion of the original genetic diversity. Similar results were found for other large and similarly interconnected populations in Brazil ( Buso, Rangel & Ferreira, 1998 ; Vaz et al, 2009 ).…”
Section: Discussionsupporting
confidence: 88%
“…Migration between sub-populations may occur at the beginning of the rainy season (May), when seeds and culms are likely carried along the river. Vaz et al (2009) reached similar conclusions and did not find evidence of structure among samples collected along the same river separated by ∼10 km. Studies that found structure ( Akimoto, Shimamoto & Morishima, 1998 ; Buso, Rangel & Ferreira, 1998 ; Brondani et al, 2005 ; Karasawa et al, 2007b ) consistently analyzed populations separated by large distances (>100 km), and in most cases in different unconnected river systems.…”
Section: Discussionsupporting
confidence: 54%
“…The highly polymorphic EST-SSR markers resulted out 121 alleles with an average of 5.5 alleles per locus, which was comparable to other studies such as 4.91 in broomcorn millet, 4.79 in sorghum, 3.93 in rice, 8.2 in maize, 6.16 and 2.4 in foxtail millet, and 7.6 in sorghum (Cho et al, 2000;Agrama et al, 2007;Hu et al, 2009;Shehzad et al, 2009;Jia et al, 2009;Lin et al, 2012). The HE mean value in the present study (0.594) was higher than that reported in proso millet (0.37), while less than that reported in rice (0.67) (De campos et al, 2008;Cho et al, 2010). Similarly, the Ho average value (0.034) was slightly closer to Indian foxtail millet (0.045) (Gupta et al, 2012).…”
Section: Discussioncontrasting
confidence: 76%
“…It grows along riverbeds and margins or as isolated populations, in lowland conditions, far from the rivers (known as marshy valleys), in which case it has a behavior typical of weeds or colonizing plants (Brondani et al, 2001). Oryza glumaepatula has been extensively studied (Vaz et al, 2009), due to its close genetic relationship to cultivated rice and, especially, because it has the potential to successfully transfer favorable yield-related alleles, promoting positive increases in cultivated rice architecture and grain yield (Brondani et al, 2002;Rangel et al, 2005). Oryza glumaepatula has been used as allele donor to elite lines (O. sativa) from the Brazilian rice breeding program since 1996 (Brondani et al, 2001).…”
Section: Introductionmentioning
confidence: 99%